2012
DOI: 10.2139/ssrn.2044464
|View full text |Cite
|
Sign up to set email alerts
|

Common Risk Factors and the Macroeconomy: New Evidence from the Japanese Stock Market

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…2 For the Japanese market, the yen-based Fama-French factors computed by Stephano Marmi 3 are considered. Past studies on the performance of the Japanese stock market reflect a mixed performance of the standard risk models (Bretschger and Lechthaler, 2014). The intercepts, excluding transaction costs, remain significantly positive for most of the 24 cases.…”
Section: Pairs Trading Without Vix Timingmentioning
confidence: 90%
“…2 For the Japanese market, the yen-based Fama-French factors computed by Stephano Marmi 3 are considered. Past studies on the performance of the Japanese stock market reflect a mixed performance of the standard risk models (Bretschger and Lechthaler, 2014). The intercepts, excluding transaction costs, remain significantly positive for most of the 24 cases.…”
Section: Pairs Trading Without Vix Timingmentioning
confidence: 90%
“…Motivated by the high book-to-market premium in Japanese stocks, Daniel et al (2001) examined the value premium of Japanese stock return over the period 1975-1997 and the results reject the Fama-French three-factor model. A more recent study by Bretschger and Bretschger and Lechthaler (2012) also observe that the CAPM model does not hold true in the Japanese stock market.…”
Section: Overview Of the Japanese Stock Marketmentioning
confidence: 95%
“…Research by Kubota and Takehara (1997) showed that the Fama French three-factor model is appropriate for the Japanese market. Likewise, Bretschger and Lechthaler (2012) examine the model using data from July 1984 to July 2009, and find that the model captures common variation in share returns. In contrast to this, research by Daniel, Titman and Wei (2001) employs data from the Tokyo Stock Exchange for the period 1971 to 1997 to test the performance of the Fama French three-factor model.…”
Section: The Fama French Three-factor Modelmentioning
confidence: 99%